2013
DOI: 10.3126/hn.v12i0.9033
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Precipitation Estimation for Hydropower Development

Abstract: Runoff is one of the major factors that govern the capacity of a hydropower project. Precipitation data are needed for estimation of runoff through runoff simulation using a hydrological model. Dense setup of rain gauge network in a mountainous topography is difficult and expensive. An alternative for this problem is the use of Satellite precipitation data with high spatial and temporal resolution. They have an additional advantage that they represent areal precipitation. But, these data should be duly evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In contrast, TRMM precipitation product underestimated the gauge observation over the Himalayan region of the country. Tamrakar and Alfredsen (2013) evaluated TRMM (3B42) for hydrological application and found that TRMM product can be used for runoff simulations over Nepal. A study over multiple complex terrain regions found that GSMaP V07 was able to detect the orographic rainfall and the rainfall amounts and outperforms IMERG V06B in Nepal with evaluation against limited stations (Derin et al, 2019), whereas evaluation based on large‐scale station network revealed that GSMaP‐Gauge product was more consistent with reproducing spatial pattern while IMERG product was more reasonable to reproduce precipitation amount over the country (Sharma, Chen, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, TRMM precipitation product underestimated the gauge observation over the Himalayan region of the country. Tamrakar and Alfredsen (2013) evaluated TRMM (3B42) for hydrological application and found that TRMM product can be used for runoff simulations over Nepal. A study over multiple complex terrain regions found that GSMaP V07 was able to detect the orographic rainfall and the rainfall amounts and outperforms IMERG V06B in Nepal with evaluation against limited stations (Derin et al, 2019), whereas evaluation based on large‐scale station network revealed that GSMaP‐Gauge product was more consistent with reproducing spatial pattern while IMERG product was more reasonable to reproduce precipitation amount over the country (Sharma, Chen, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Highly varied topography and a large elevation gradient over a short latitudinal distance in Nepal have given rise to a distinct climate over a small area, producing several physiographic zones (Fig. 1), with larger variation in precipitation pattern (Tamrakar and Alfredsen 2013). Southeasterly monsoon arriving from the Bay of Bengal dominates overall climate of Nepal, providing 80% of annual precipitation during summer months from June to September (Shrestha and Aryal 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Climatic regimes similarly vary from subtropical in the southern plains to the alpine in the high mountains [18]. Large variation of precipitation occurs even over small distances due to highly undulating surface topography with high mountains and deep valleys [21]. Analysis of observed precipitation data in Nepal is very limited and one of the reasons for this is the relatively short period of data availability [17].…”
Section: Introductionmentioning
confidence: 99%